2018
DOI: 10.1002/suco.201800156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of steel fiber reinforced recycled aggregate concrete

Abstract: This study experimentally investigates the mechanical properties of steel fiber reinforced recycled aggregate concrete (SFRRAC). The smaller strength and ductility of recycled aggregate concrete (RAC), compared to those of natural aggregate concrete (NAC), have restricted its use to mainly non‐structural applications in the construction industry. Such limitations in the mechanical behavior of RAC can be overcome by adding industrial steel fiber (SF). In this study, the split‐tensile strength, the compressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 31 publications
1
37
0
2
Order By: Relevance
“…The studies in the literature differ on how compressive strength is affected when steel fibers are added to RCA, as it may cause an increase or reduction [ 27 , 29 , 30 , 34 , 60 , 66 , 86 ]. Tensile and flexural strength are improved when fibers are added to RCA, regardless of the type of fiber [ 29 , 30 , 34 , 40 , 60 , 66 , 86 ]. However, other studies have concluded that steel fibers have an inconsiderable effect on mechanical properties in RCA [ 27 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies in the literature differ on how compressive strength is affected when steel fibers are added to RCA, as it may cause an increase or reduction [ 27 , 29 , 30 , 34 , 60 , 66 , 86 ]. Tensile and flexural strength are improved when fibers are added to RCA, regardless of the type of fiber [ 29 , 30 , 34 , 40 , 60 , 66 , 86 ]. However, other studies have concluded that steel fibers have an inconsiderable effect on mechanical properties in RCA [ 27 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the last few decades, steel fiber is commonly used as main constituent material in FRCC 13–16 . Steel fibers are used to improve the tensile strength, flexural strength, energy absorption capability as well as cracking arresting properties, stiffness, deflection capability, and postcracking behavior 17–21 . The wide range of availability and practical affordability of steel fibers make it a popular choice for its use in concrete composite applications 22 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the studies on the mechanical properties of steel fiber reinforced concrete with recycled coarse aggregate (SFRCAC) mainly focus on the basic mechanical properties, such as Ramesh [ 22 ] investigated the split-tensile strength, compressive strength, the toughness under compression and the elastic modulus for 25 SFRCAC mixes. In addition, Gao et al [ 23 , 24 , 25 , 26 ] studied the compressive strength, flexural strength, durability and mixture proportion design method by taking the replacement ratio of reclaimed aggregate and the volume content of steel fiber as the influencing parameters.…”
Section: Introductionmentioning
confidence: 99%